Seawater temperature effect on metal accumulation and toxicity in the subantarctic Macquarie Island isopod, Exosphaeroma gigas - A Lewis; CK King; NA Hill; A Cooper; AT Townsend; Julie Mondon (2016)
Very little is currently known of subantarctic nearshore invertebrates' sensitivity to environmental metals and the role of temperature in this relationship. This study investigated Cu and Zn toxicity in the common subantarctic intertidal isopod, Exosphaeroma gigas, and the influence of temperature on Cu toxicity and bioaccumulation kinetics. Adult E. gigas are insensitive to Cu and Zn at concentrations of 3200 and 7400μg/L respectively in non-renewal tests at 5.5°C (ambient subtidal temperature) over 14days. Under renewed exposures over the same temperature and time period the LC50 for copper was 2204μg/L. A 10-fold increase in Cu body burden occurred relative to zinc, indicating E. gigas has different strategies for regulating the two metals. Copper toxicity and time to mortality both increased with elevated temperature. However, temperature did not significantly affect Cu uptake rate and efflux rate constants derived from biodynamic modelling at lower Cu concentrations. These results may be attributable to E. gigas being an intertidal species with physiological mechanisms adapted to fluctuating environmental conditions. Cu concentrations required to elicit a toxicity response indicates that E. gigas would not be directly threatened by current levels of Cu or Zn present in Macquarie Island intertidal habitats, with the associated elevated temperature fluctuations. This study provides evidence that the sensitivity of this subantarctic intertidal species to metal contaminants is not as high as expected, and which has significance for the derivation of relevant guidelines specific to this distinct subpolar region of the world.